2021
DOI: 10.3390/jmse9030272
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Reef Topography on Storm-Driven Sand Flux

Abstract: Natural formations of rock and coral can support geologically controlled beaches, where the beach dynamics are significantly influenced by these structures. However, little is known about how alongshore variations in geological controls influence beach morphodynamics. Therefore, in this study we focus on the storm response of a beach (Yanchep in south Western Australia) that has strong alongshore variation in the level of geological control because of the heterogeneous calcarenite limestone reef. We used a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Beach morphodynamics in a geologically controlled area from calcarenite limestone reefs were investigated by Bosserelle et al [8]. Numerical experiments during a winter storm event were carried out using a modified version of the XBeach model at Yanchep beach in Southwest Australia.…”
Section: • Numerical Modelling For Hydro-morphodynamic Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Beach morphodynamics in a geologically controlled area from calcarenite limestone reefs were investigated by Bosserelle et al [8]. Numerical experiments during a winter storm event were carried out using a modified version of the XBeach model at Yanchep beach in Southwest Australia.…”
Section: • Numerical Modelling For Hydro-morphodynamic Processesmentioning
confidence: 99%
“…Numerical experiments during a winter storm event were carried out using a modified version of the XBeach model at Yanchep beach in Southwest Australia. The modification of the model formulation included considering different values for the bottom dissipation parameter (see f w in Equation (1) [8]) and the bed friction parameter (see c f in Equation ( 2) [8]) for sandy and reef outcrops. Simulated currents showed that the model was twice as sensitive to roughness than wave braking parameters, and three-times more sensitive to the roughness than to the roller dissipation viscosity factor (see Table 4 [8]).…”
Section: • Numerical Modelling For Hydro-morphodynamic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In many coasts, natural reefs are interposed offshore, safeguarding the sedimentary stability of the sandy beaches [13,14]. Rocky and erosional coastal environments support sedimentary deposits and beaches of very diverse characteristics, controlled by complex geological structures and their erosion-deposition dynamics [15].…”
Section: Introductionmentioning
confidence: 99%